Keeping fresh fruit and vegetables clean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Philip Siamuyoba, a senior agricultural officer for horticultural crops in the Zambian ministry of agriculture, on the basic principles farmers should follow to keep their produce free from harmful contaminants.